2005
DOI: 10.1016/j.antiviral.2005.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Development of antiviral therapy for severe acute respiratory syndrome

Abstract: A new disease, the severe acute respiratory distress syndrome (SARS), caused by the SARS coronavirus (SARS-CoV), emerged at the beginning of 2003 and rapidly spread throughout the world. Although the disease had disappeared in June 2003 its re-emergence cannot be excluded. The development of vaccines against SARS-CoV may take years. Therefore, the availability of effective antiviral drugs against SARS-CoV may be crucial for the control of future SARS outbreaks. In this review, experimental and clinical data ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 183 publications
(201 reference statements)
0
53
0
1
Order By: Relevance
“…Glycyrrhizin, a triterpene saponine, is a constituent of licorice root. It has been found to interfere with replication and/or cytopathogenic effect (CPE) induction of many viruses including respiratory viruses, such as respiratory syncytial virus, SARS coronavirus, and influenza viruses [23][24][25][26][27][28]. Moreover, antiinflammatory and immunomodulatory properties were attributed to glycyrrhizin [26].…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin, a triterpene saponine, is a constituent of licorice root. It has been found to interfere with replication and/or cytopathogenic effect (CPE) induction of many viruses including respiratory viruses, such as respiratory syncytial virus, SARS coronavirus, and influenza viruses [23][24][25][26][27][28]. Moreover, antiinflammatory and immunomodulatory properties were attributed to glycyrrhizin [26].…”
Section: Introductionmentioning
confidence: 99%
“…6 To date, SARS-CoV 3CL pro inhibitors have been reported from both synthetic peptidyl compound libraries and natural product derived libraries. 7 Inhibitory synthetic compounds include C2-symmetric diols, 8 quinolinecarboxylic acids, 9 isatins, 10 and anilides. 11 Natural-derived inhibitors include betulinic acid, 12 indigo, 13 aloeemodin, 13 luteolin, 7 and quinine-methide triterpenoids; the latter are products of our latest investigation 3CL pro inhibitor from Tripterygium regelii.…”
Section: Introductionmentioning
confidence: 99%
“…Although in the 2 years since the discovery of SARS much has been learnt about its pathogenesis, epidemiology and laboratory diagnosis, progress has been less rapid in other areas, particularly in establishing an antiviral treatment for patients. Steroids with or without ribavirin have been widely employed in the treatment of SARS but have not been very effective [2,3] . However, several studies have reported that type I interferons (IFNs) can inhibit SARS replication in vitro [4] and, specifically, that IFN-␤ exhibits the most potent anti-SARS-CoV activity in Vero cells, showing levels of inhibition at concentrations of 1,000 IU/ml or greater [5][6][7][8] .…”
mentioning
confidence: 99%